FAKTOR – FAKTORoYANG BERHUBUNGANoDENGAN STRES KERJA PADAoOPERATOR SPBU DI KECAMATAN TEMBALANG SEMARANG (Studi Kasus Pada Pekerja SPBU Bagian Operator di Kecamatan Tembalang Semarang) - Novena Claudya Simanullang; Ida Wahyuni; Daru Lestantyo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The operator of fuel station is kind of work that fill the needs of the community in transportation needs. Needs of Tembalang sub-district to fuel is quite high due to activities that require high mobility. The number of consumers, diverse consumer, work shifts, environmentaloconditions, and conflicts that occur in workers can cause work stress. The purposeoof this study was to analyze theofactors that associated with work stress. This research used explanatory research method with quantitative method. The population in this study were all workers which amount 34 people and performed on the workers population. The instrument of this research is research questionnaire, book of NASA TLX, manual of HRS-A, and procedure of SNI 7269: 2009. Result of research indicate there is 52,9% sample. Data analysis used Chi-Square test. The test showed there was assosiationobetweenomental workload variable (p = 0,008), individual role (p = 0,009) and career development (p = 0,044) with work stress. To minimize work stress, company can designed break room with music player or television, create events to refresh and maintain good relationships such as exercise and eating together, and involving workers in the distribution of the work schedule.